(untitled) (Bulletin of criminological association of Ukraine, 2025)
The analysis of theoretical approaches, taking into account the features of criminal illegal activity, allowed us to reasonably indicate that the content of the forensic characteristics of criminal offenses related to smuggling must necessarily include information about: 1) the subject of smuggling and its size (volume/quantity), which affects the qualification of the criminal offense; 2) the method of committing smuggling (preparation, direct commission and concealment); 3) the specifics of the situation (in particular, whether the criminal offense was committed outside customs control or with concealment from customs control); 4) the characteristics of the individual criminal, members of criminal groups involved in committing smuggling; 5) traces of criminal illegal activity. Information about these elements becomes a proper basis for building all other elements of the forensic methodology for investigating criminal offenses related to smuggling. We believe that in the future, attention should be paid to specific features that characterize these elements.